PENGARUH VOLUME DAN NILAI TRANSAKSI TERHADAP INDEKS HARGA SAHAM PAPAN PENGEMBANGAN DI BURSA EFEK INDONESIA - Sunarso Sunarso (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2017)
This research is aimed to find out corelation of book value and transaction volume to of development board stocks price index (DBX) index. On development board stocks, managing risks in the Indonesian Capital Market is different with main board stocks, so the common existing strategy is no more suitable for DBS’s because their price can be changed extreemly in short time. That is why this research is held. Invesment can be said as the sacrefice of today consumtion to to rise capital gain in the future. There are many form of investment instruments, one of them is to buy stock in the capital market. Invesment in the form of a set of stocks is called portfolio investment. To get optimum return in the portfolio invesment an effective strategy must be implemented. One of the strategy is to compose portfolio in volatile price stocks. By implementing the strategy investor should manage risk to avoid excessive loss in their investment. The methood in this research quatitative reseach base on secondary data source. The data taken from monthly historical transaction and fundamental analysis of DBX form Jaly 2011 to June 2016. Base on this research the volume and value of transacion only influence 25% of the DBX in Indonesian Stock Exchange. Keywords:Book Value, Transaction Volume, Development Board Stocks, capital market, portfolio invesment